2010
DOI: 10.1530/rep-10-0022
|View full text |Cite
|
Sign up to set email alerts
|

Luteogenesis during the estrous cycle in Asian elephants (Elephas maximus)

Abstract: The occurrence of multiple corpora lutea (CLs) in the ovaries of the cycling and pregnant elephant, a monovulatory mammal, has driven scientific discussions during the past five decades. However, fundamental knowledge on luteogenesis is lacking. In this long-term study, CL formation and regression throughout the estrous cycle were monitored using transrectal 2D-and 3D ultrasonography in 33 captive Asian elephants. Serum or urinary progestagens (P m ) were measured to determine the reproductive cycle stage. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 40 publications
5
57
0
2
Order By: Relevance
“…Active secretion of PRL might play an important role for the maintenance of pregnancy in elephants [58]. Pregnant African and Asian elephants possess multiple corpora lutea in their ovaries throughout gestation [21,[59][60][61]. Allen et al demonstrated that the placenta of the elephant is steroidogenically inert [31].…”
Section: Discussionmentioning
confidence: 99%
“…Active secretion of PRL might play an important role for the maintenance of pregnancy in elephants [58]. Pregnant African and Asian elephants possess multiple corpora lutea in their ovaries throughout gestation [21,[59][60][61]. Allen et al demonstrated that the placenta of the elephant is steroidogenically inert [31].…”
Section: Discussionmentioning
confidence: 99%
“…(b) Ultrasound A total of 336 transrectal ultrasound examinations were performed using previously reported approaches [13,25,26]. Five Asian elephants were ultrasonographically examined on random days during the entire pregnancy and in one case until day 459.…”
Section: (A) Elephantsmentioning
confidence: 99%
“…We showed previously that during the six-week-long follicular phase of the oestrous cycle, the acCLs are derived from luteinized unruptured follicles [26]. Luteinization of the first wave of follicles is induced by the first, anovulatory LH peak.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In pregnant elephant, in contrast, mature follicles are rarely, if ever, seen in the maternal ovaries (Perry 1964, Short & Buss 1965, Laws 1969, Hodges 1998, Allen 2006 and it is now proposed that the accessory CLs of pregnancy first form as a result of luteinisation of small (0.8-1.2 cm) follicles that develop in response to the first of the two peaks in serum LH concentrations which characterise the 20-22 day inter-luteal period of the elephant oestrous cycle (Lueders et al 2010(Lueders et al , 2011. These accessory luteal structures, seen clearly by serial transrectal ultrasonographic examinations of the maternal ovaries (Lueders et al 2011), form predominantly, but not exclusively, on the ovary ipsilateral to the uterine horn that will contain the conceptus (Allen et al 2002), and they apparently remain dormant (and non-secretory) during the remainder of the inter-luteal phase, the release of the second ovulation-inducing LH peak (Kapustin et al 1996, Brown et al 1999) and early gestation.…”
Section: Introductionmentioning
confidence: 99%